2020
DOI: 10.1186/s12957-020-1811-5
|View full text |Cite
|
Sign up to set email alerts
|

The value of MRI in management of endometrial hyperplasia with atypia

Abstract: Background: The value of the magnetic resonance imaging (MRI) in the assessment of women with endometrial hyperplasia and its role in diagnosis of myometrial invasion or coexistence of cancer is not known. This study aimed to evaluate the accuracy and usefulness of MRI in the management of patients diagnosed on endometrial biopsy with complex endometrial hyperplasia with atypia (CEHA). Methods: A retrospective study of 86 cases diagnosed with endometrial hyperplasia with atypia on the initial endometrial biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…The results of the scoping review were reported according to the Preferred Reporting Items for Systematic reviews and Meta-criteria and were included in our review. We included 24 primary studies, [9][10][11][13][14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] three meta-analyses, [17][18][19] and one poster presentation. 12 The characteristics of the 28 included studies are shown in Table 2.…”
Section: Stage 5: Summarizing Resultsmentioning
confidence: 99%
“…The results of the scoping review were reported according to the Preferred Reporting Items for Systematic reviews and Meta-criteria and were included in our review. We included 24 primary studies, [9][10][11][13][14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] three meta-analyses, [17][18][19] and one poster presentation. 12 The characteristics of the 28 included studies are shown in Table 2.…”
Section: Stage 5: Summarizing Resultsmentioning
confidence: 99%
“…Alternatives to PET/CT include magnetic resonance imaging (MRI). It, however, has been shown to have low specificity (15.4%) and positive predictive value (50%) in characterizing malignant transformation in women with precancerous endometrial lesions [35]. In another retrospective study, MRI failed to identify 9 out of 21 patients with endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We considered that, at this stage of endometrial pathology, it does not provide significant data. Recent studies show that magnetic resonance imaging (MRI) is not considered an effective way to identify invasive lesions in EH cases and can give false positive results in 46% of cases [12,50,83].…”
Section: Discussionmentioning
confidence: 99%
“…Factors that increase the risk of malignancy in endometrial tissue include obesity, diabetes (DM) and high blood pressure (HBP) [11]. However, it is estimated that the incidence of EH is at least three times higher than of the EC [12].…”
Section: Introductionmentioning
confidence: 99%